High-Resolution, Sensitivity-Enhanced Active Resonator Sensor Using Substrate-Embedded Channel for Characterizing Low-Concentration Liquid Mixtures - Mohammadi, Sevda; Adhikari, Kishor Kumar; Jain, Mandeep Chhajer; Zarifi, Mohammad H. (IEEE transactions on microwave theory and techniques, 2022)
Sensitivity and resolution are important parameters that pose a significant challenge in using microwave microfluidic sensors to monitor low-concentration binary liquid mixtures. This work presents a microwave split-ring resonator (SRR) sensor equipped with a substrate-embedded fluidic channel and an active feedback loop to enhance sensitivity and resolution, respectively. The substrate-embedded channel eliminated the impact of the liquid-carrying tubes' wall and maintained a significant interaction between the liquid in the channel and the electromagnetic (EM) field confined between the SRR and ground plane. Therefore, embedding the channel inside the substrate of the SRR sensor, operating at 2.63 GHz, enhanced the sensitivity by 60%. The constructive energy from the active feedback loop boosted the quality factor of the passive SRR by over 100× (from 116 to 13 000), which significantly enhanced the resolution of the sensor. As a proof of concept, two prototypes of the sensor having different substrate-embedded channels with cross-sectional diameters of 1 and 0.762 mm were fabricated and used to detect low concentrations of ethanol (0-0.08 vol%) and salt (0-200 mM) in water. Embedding the channel inside the substrate of the active SRR sensor achieved a linear correlation ( R^{2} = 0.99 ) between the resonant frequency and the concentration of ethanol and salt in water with high sensitivity (19.95 MHz/vol% for ethanol and 4.35 kHz/mM for salt) and resolution (0.001 vol% for ethanol and 2.298 mM for salt). The achieved results demonstrate the feasibility of using the active SRR microwave sensor with a substrate-embedded channel for monitoring ethanol in fermentation broths and electrolytes in human sweat.